Humanistic Characterized Liturgical Service - Krismiyanto, Alfonsus; Laka, Laurensius; Maeja, Jhon Daeng (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2025)
Religion and science can be combined. Even though in the course of time, the two have been at odds with each other. One of the things that can be combined is humanistic psychology and liturgy. Humanistic psychology can support service to the people in the liturgy. However, not all parties are aware of this. One of them is the liturgical ministers at Maria Ratu Damai Purworejo Parish have not realized and practiced humanistic psychology in their ministry. The purpose of this PkM activity is to introduce the field of humanistic psychology to liturgical ministers. The methods used are socialization and guidance. The result of PkM activities is that the liturgical ministers know humanistic psychology. Liturgy is a form of self-actualization. Liturgical ministers can also humanize people in the liturgy. In addition, the Catholic family must have social cohesion in the liturgy. This cohesion will provide encouragement to litrgui servants. The conclusion of PkM activities is that humanistic psychology can be used in liturgy. Science and religion can be combined for ministry activities.